The likability trap : how to break free and succeed as you are - Menendez, Alicia (Harper Business, 2019)
"Women are perceived as either strong and cold or weak and warm. An award-winning journalist and cohost of PBS's Amanpour and Company examines likability and empowers readers to reject an outdated image of leadership instead of reinventing themselves"--